HUBUNGAN BERAT LAHIR BAYI DENGAN RUPTURE PERINEUM PADA PERSALINAN NORMAL DI PUSKESMAS TEGALREJO YOGYAKARTA 2015 - Resmawati - (Jurnal Ilmiah Maternal, 2017)
ABSTRACT  Research Background: The prevalence of mothers who have a ruptured perineum in Indonesia in the age group of 25-30 years is 24 %, while the maternal age of 32-39 years by 62 % . As a result of the mother's perineum rupture that 10 % of women feel pain that ended after 3-18 months of delivery , 20% of women experience pain during coitus approximately 3 months , 3-10 % of mothers reported bowel incontinence , 20 % had urinary incontinence , anal sphincter damage sketchy occurred in 36 % although the third and fourth degree laceration repair. Research purposes: To determine the relationship with the baby's birth weight on the perineum rupture normal deliveries at health centers Tegalrejo Yogyakarta, 2015. Research Method: This research uses descriptive method correlative with cross sectional method. The independent variable was birth weight babies and the dependent variable is the rupture of the perineum in normal birth mothers. The population in this study was 158 people. The sampling technique is purposive sampling as many as 95 people. Retrieving data using tables and master data analysis using Spearman Rank correlation. Research Result: Statistical test results obtained correlation coefficient of 0.247 with p-Value amounted to 0,016 with significance level of 0.016 (α 0.05). Conclusion and Suggestion: There is a relationship with the baby's birth weight rate of rupture of the perineum in normal deliveries at health centers Tegalrejo Yogyakarta in 2015 with a low level of closeness. For midwife is hoped can complete all encode for processing of patient.    Keywords : Baby Born Weight, Ruture Perineum , Normal PartumBibliography                 : 11 books ( 2008-2015 ) , 3 journals Pages                              : 6 pages, 4 tables  1Research Title2Student of Diploma IV Midwifery Program, Faculty of Health Science, 'Aisyiyah University of Yogyakarta